(untitled) (Моделювання, керування та інформаційні технології, 2021)
The mathematical problem of the steady-state biofiltration of an organic substrate is formulated at two levels taking into account the limitation and inhibition of the rate of its decomposition. The exact and approximate solutions to the problem of substrate biooxidation in a representative biofilm were obtained and compared using test examples. Based on them an analysis of the technological process in the porous biofilter medium and the output characteristics was carried out.